The Ethics of Responsibility at Levinas - sifi, feyrouz; zerroukhi, drradji (Journal of Social Sciences and Humanities, 2021)
Moral thought evolved in contemporary Western philosophy to culminate in the birth of heterosexualism, which in turn paved the way for the emergence of the ethics of responsibility forleVinas. These morals are based on respect for the other. To seek life, and to preserve it for the ego and others, And this philosophy is worthy of attention and application on the ground to achieve lasting peace, so it can be separated by saying that the ethics of responsibility are the ethics that establish the universality in which a person is respected away from his ideology and race, and that the ethics of responsibility calls for an asymmetric responsibility and is a responsibility impartial in the sense that A person bears his responsibility and does his duty towards others without waiting for any return from them and without waiting for them to exchange it with the same feeling, it is the responsibility of his freedom from all the goals and benefits, And the ethics of responsibility is the one that establishes the ethics of heterosexuality, which liberates a person from conflict and killing, and also liberates a person from hatred and hatred. To transform into realistic social and political behavior. It is only through this transformation that lasting peace will be achieved, wars will end and tolerance and universal brotherhood that man has long sought to achieve happiness will prevail. Responsibility towards the other means the impossibility of leaving this person alone before death and for the self to become a responsibility that cannot escape this responsibility. Moral responsibility does not arise between a person of this type and a person of this type, but responsibility arises whenever the self-encounters any human being and before thinking about Knowing what she must do, the other one who needs me imposes himself,And he asks through his starvation through his weakness to be by his side, and I can only meet this call, so this self-vision of the poor and weak other makes them think first and foremost of what they can do for the sake of the other and for his service, this The moral obligation towards the weak, the neglected, the stranger, the orphan and the widow arises from the fact that the stranger is the person who has nothing to do with me, but despite that he cares about me and as if it is part of me and must bear responsibility towards him away from every interest or benefit